Aberrant intracellular metabolism of T‐DM1 confers T‐DM1 resistance in human epidermal growth factor receptor 2‐positive gastric cancer cells. Issue 7 (23rd May 2017) - Wang, Hongbin; Wang, Wenqian; Xu, Yongping; Yang, Yong; Chen, Xiaoyan; Quan, Haitian; Lou, Liguang
Abstract : Trastuzumab emtansine (T‐DM1), an antibody–drug conjugate (ADC) consisting of human epidermal growth factor receptor 2 (HER2)‐targeted mAb trastuzumab linked to antimicrotubule agent mertansine (DM1), has been approved for the treatment of HER2‐positive metastatic breast cancer. Acquired resistance has been a major obstacle to T‐DM1 treatment, and mechanisms remain incompletely understood. In the present study, we established a T‐DM1‐resistant N87‐KR cell line from HER2‐positive N87 gastric cancer cells to investigate mechanisms of acquired resistance and develop strategies for overcoming it. Although the kinetics of binding, internalization, and externalization of T‐DM1 were the same in N87‐KR cells and N87 cells, N87‐KR was strongly resistant to T‐DM1, but remained sensitive to both trastuzumab and DM1. T‐DM1 failed to inhibit microtubule polymerization in N87‐KR cells. Consistently, lysine‐MCC‐DM1, the active T‐DM1 metabolite that inhibits microtubule polymerization, accumulated much less in N87‐KR cells than in N87 cells. Furthermore, lysosome acidification, achieved by vacuolar H + ‐ATPase (V‐ATPase), was much diminished in N87‐KR cells. Notably, treatment of sensitive N87 cells with the V‐ATPase selective inhibitor bafilomycin A1 induced T‐DM1 resistance, suggesting that aberrant V‐ATPase activity decreases T‐DM1 metabolism, leading to T‐DM1 resistance in N87‐KR cells. Interestingly, HER2‐targeted ADCs containing a protease‐cleavable linker, such as hertuzumab‐vc‐monomethyl auristatin E, were capable of efficiently overcoming this resistance. Our results show for the first time that a decrease in T‐DM1 metabolites induced by aberrant V‐ATPase activity contributes to T‐DM1 resistance, which could be overcome by HER2‐targeted ADCs containing different linkers, including a protease‐cleavable linker. Accordingly, we propose that V‐ATPase activity in lysosomes is a novel biomarker for predicting T‐DM1 resistance. Abstract : To date, acquired resistances arise to be a major obstacle to T‐DM1 treatment and mechanisms remain incompletely understood. Our results demonstrate for the first time that T‐DM1 metabolites reduction induced by V‐ATPase aberation contributes to T‐DM1 resistance, which could be overcome by HER2‐targeted ADC with different linkers including protease‐cleavable linker, and we propose V‐ATPase activity in lysosomes as a novel biomarker to predict T‐DM1 resistance.